Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Kepatuhan Wajib Pajak Orang Pribadi Di Kota Salatiga - Safaah, Nailis; Mayasari, Elsa; Hasanah, Musyarofatun; Kabib, Nur (Journal of Principles Management and Business, 2022)
This research is intended to determine the effect of tax knowledge, socialization and application of e-filling on individual taxpayer compliance. The population used in this research is individual taxpayers in Salatiga City. While in determining the sample using the formula from Roscoe by multiplying the number of variables by 10, so that the total sample used is 40 respondents. Furthermore, the data analysis technique used for testing is multiple linear regression analysis using SPSS 23 software. From the results of data processing, the results show that partially tax knowledge and the application of e-filling have a positive and significant influence on taxpayer compliance. While the socialization variable is not able to influence the level of taxpayer compliance. Next, simultaneously the three independent variables, namely knowledge of taxation, socialization and application of e-filling have a positive and significant impact on the level of compliance of individual taxpayers.